PENGARUH SKEPTISME PROFESIONAL, ETIKA DAN PENGALAMAN AUDIT TERHADAP KETETAPAN PEMBERIAN OPINI OLEH AUDITOR - eka kusuma dewi; Mila Ramadhani (LPPM Universitas Putera Batam, 2018)
This study aims to determine how Professional Skepticism, Ethics, and Audit Experience for Provision of Opinion Assessment by The Auditor firm in Tangerang Cist and South Tangerang. Sampling using simple random sampling technique, used in this study were 50 external auditors of 6 public accounting firms Tangerang Kota dan South Tangerang. The data used are primary data in the form of a questionnaire distributed directly to the respondent. Methods of data analysis used in this research is multiple linear regression analysis, descriptive statistical test and classical assumption. Partial test results indicate that Professional Skepticism, Ethics, and Audit Experience is affected positively to Provision of Opinion Assessment by The Auditor. While the simultaneous test results showed that Professional Skepticism, Ethics, and Audit Experience together affect to the Provision of Opinion Assessment by The Auditor